Estimation of Activation Energy of Desorption of n-Hexanol from Activated Carbons by the TPD Technique - Zhong Li; Hongjuan Wang; Hongxia Xi; Qibin Xia; Jinglei Han; Lingai Luo (Adsorption Science & Technology)
Activated carbon and five kinds of metal-ion-substituted activated carbons, viz. Ag + -activated carbon, Cu 2+ -activated carbon, Fe 3+ -activated carbon, Ba 2+ -activated carbon and Ca 2+ -activated carbon, were prepared. A model for estimating the activation energy of desorption was established. Temperature-programmed desorption (TPD) experiments were conducted to measure the TPD curves of n-hexanol and hence estimate the activation energy for n-hexanol desorption from the various activated carbons. The results showed that the activation energies for n-hexanol desorption from the Ag + -activated carbon, the Cu 2+ -activated carbon and the Fe 3+ -activated carbon were higher than those from the unsubstituted activated carbon, the Ca 2+ -activated carbon and the Ba 2+ -activated carbon.